(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Previous studies in the field of pragmatics discussed the phenomenon of politeness as having a polite/impolite distinction. In this study, an attempt is to be done to focus on the brighter side of impoliteness having semi-polite utterances. Thus, the major concern of this study is to consider some impolite utterances as being valuable for our everyday life situations. The idea is that people agreed upon the rejection of impolite utterances, even, they educate children to avoid such utterances and expressions. Throughout this study, impolite ( purposively termed ’ politely-oriented ) utterances are investigated in the literature, then, a military discourse will be analyzed (the aim) to reach the phenomenon. The reason behind choosing such a discourse is that it is naturally built of using such utterances. In the world of military, militants achieve numerous functions by impolite use of language. The study consists of four sections. Each section deals with a different dimension of functionality of impolite utterances. It is hypothesized that impoliteness can functionally be used to attain certain goals.